Decreased first-pass metabolism of labetalol in chronic liver disease. Issue 6144 (14th October 1978) - Homeida, M; Jackson, L; Roberts, C J
Abstract : The effect of chronic liver disease on the rate of elimination and extent of "first-pass" metabolism of labetalol was studied. Pharmacokinetic measurements were made after both oral and intravenous administration to seven healthy subjects and to 10 patients with chronic liver disease. Plasma half life was similar in the two groups. Plasma concentrations were considerably higher in the patients than in the healthy subjects after oral administration but similar after intravenous injection. Thus the bioavailability of labetalol was increased in liver disease due to reduced first-pass metabolism. Bioavailability in the group of patients correlated negatively with serum albumin concentration. There were falls in supine heart rate and blood pressure which tended to be greater after oral administration in the patients with liver disease, suggesting an exaggerated response related to the increased bioavailability. Oral dosage requirements of labetalol and possibly other drugs susceptible to first-pass metabolism are reduced in the presence of liver disease.